From idea to innovation : a handbook for inventors, decision makers and organizations - Weis, Bernd X. (Management for Professionals,, 2015)
The book assists in bringing together the three stakeholders of an innovation - inventor, decision maker and organization. These stakeholders have conflicting requirements and the book offers advice on how and by what methods they can communicate and the information that is expected and required in different phases of innovation. The perspectives of inventor, decision maker and organization are integrated in a business model that enables a common "language" and communication platform for the inevitably emerging tension field and that allows for asking and answering the right questions.